Assessment of the Diversity in Fruit Yield and Fruit Components among Sri Lanka Tall Coconut Accessions Conserved Ex-Situ - Perera, K. N. S.; Herath, H. M. N. B.; Attanayaka, D. P. S. T. G.; Perera, S. A. C. N. (International Coconut Community, 2015)
Characterization of conserved coconut germplasm has been undertaken globally for identification of important features of different accessions for them to be effectively used in coconut breeding. One hundred and fifty seven accessions comprising of local and exotic material have been conserved in ex-situ field genebanks of Coconut Research Institute in Sri Lanka. The objective of this study is to quantitatively characterize nut yield and fruit components by weights among Sri Lanka Tall (Typica) coconut accessions. Twenty local tall coconut accessions were characterized for nut yield and fruit components following Bioversity International descriptors for coconut. Bunch wise nut yield was recorded in all the coconut phenotypes in the six most mature bunches in 25 randomly selected palms from each accession. Sampled nuts were scored for weights of fresh nut, husked nut, split nut and kernel and the weights of husk, water and shell of each nut were derived from the scored data. Analysis of variance by general linear models procedure and mean separation by Duncan’s multiple range test were performed in SAS v8 and principal component analysis and cluster analysis using squared Euclidean distances were performed in Minitab V17. General linear models procedure revealed significant differences for nut yield and all the fruit components at 5% probability level. Walahapitiya recorded the highest average nut yield followed by the Razeena with statistically equal performances. Clovis recorded the highest values for most of the parameters for fruit component analysis followed by the accession Margaret, grouping together in Dendogram and the scatter plot. The highest per nut kernel producer, Clovis, was followed by Margaret with statistically equal performances and this is important because kernel is the main economically important component followed by the husk. Results revealed that there is no significant correlation between nut yield and all the fruit components in tall accessions indicating the importance of taking these two parameters separately to formulate germplasm conservation strategies.